Exploring How Compatible QRIS Adoption is in The Role of Trust, Security, and Compatibility - Liban Isak Mohamed (Universitas Muhammadiyah Purwokerto, 2024)
This study examines the adoption of the Quick Response Code Indonesian Standard (QRIS) among micro, small, and medium enterprises (MSMEs) in Indonesia, focusing on the roles of trust, security, and compatibility. Utilizing a quantitative research approach, data were collected from 54 respondents of Universitas Muhammaddiyah Purwokerto Students, and analyzed using SmartPLS. The findings reveal that perceived security significantly influences compatibility, whereas trust exhibits a less pronounced impact. These results highlight the importance of robust security measures in fostering QRIS adoption, supported by theoretical frameworks such as the Technology Acceptance Model (TAM) and Transaction Cost Theory. Practical implications include prioritizing security enhancements and educational initiatives to improve digital literacy. The study contributes to understanding digital payment adoption dynamics and offers a foundation for optimizing QRIS implementation in emerging markets.